2019
DOI: 10.21037/atm.2019.03.65
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbation of interstitial lung disease after radical surgery for lung cancer: a case report

Abstract: A 69-year-old male patient underwent a left upper lobectomy for lung cancer, showing slight interstitial changes in the lung before surgery. He suffered fever with cough and expectoration postoperatively, and high-resolution computed tomography (HRCT) of the thorax indicated that the interstitial lesion in the lung was aggravated. The course of the disease progressed rapidly, and treatment that included anti-infection and steroid pulse therapy was ineffective. We conducted a retrospective analysis of the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The score of each dimension takes the average of the scores of all items in this dimension (1-7). The total score is the sum of the average scores of all three dimensions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). All the patients enrolled in this study completed the LCQ-MC one day before surgery, one month after surgery, and three months after surgery under the guidance of two trained thoracic medical staff.…”
Section: Evaluation Methods and Grouping Criteria For Coughingmentioning
confidence: 99%
See 1 more Smart Citation
“…The score of each dimension takes the average of the scores of all items in this dimension (1-7). The total score is the sum of the average scores of all three dimensions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). All the patients enrolled in this study completed the LCQ-MC one day before surgery, one month after surgery, and three months after surgery under the guidance of two trained thoracic medical staff.…”
Section: Evaluation Methods and Grouping Criteria For Coughingmentioning
confidence: 99%
“…CAP refers to a dry cough that lasts no less than two weeks after pulmonary resection, except for nasal drip syndrome, bronchial asthma, or oral angiotensin-converting enzyme inhibitor (ACEI) drugs, the chest X-ray revealed no apparent abnormality (2). Previous studies have reported the incidence of CAP can reach 25-50%, and the probabilities of coughing within one year and five years after surgery are over 50% and 18%, respectively (3). The postoperative cough can last a long time.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, early and adequate breathing exercises are significantly important to the reconstruction of lung function, improvement of hypoxemia, and improvement of sleep quality. However, we discovered from clinic practice that the completeness of breathing exercise plans for patients discharged from the hospital is normally low, which is commonly related to the heavy beating exercise progress and low self-consciousness degree of patients [4]. e conventional nursing mode lacks continuity guidance and systematic follow-up after discharge and cannot meet the needs of postoperative respiratory exercise for patients with lung cancer at the present stage [5].…”
Section: Introductionmentioning
confidence: 99%